ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA PADA IBU HAMIL DI RSIA SITTI KHADIAH 1 PERIODE AGUSTUS-OKTOBER 2019 - Alifia Nurdani Darmawan; Andi Tihardimanto; Najamuddin (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Preeclampsia is a pregnancy-specific syndrome in the form of decreased organ perfusiondue to vasospasm and endothelial activation. Preeclampsia is a major cause of maternaldeath in the world and is still a threatening problem in pregnancy, especially in developingcountries. The purpose of this study was to describe the factors associated with the incidenceof preeclampsia in pregnant women at RSIA Sitti Kharga 1 Period August-October 2019.This type of research was analytic observational with a cross sectional approach usingprimary data (questionnaires) with interview technique methods. and secondary data, namely(medical records). The research method used the "chi square" statistical test which obtainedP-value <0.05 for the three research variables, which means that there is a significantrelationship between maternal age, history of hypertension, and previous history of maternalpreeclampsia. The conclusion is that there is a significant relationship between maternal age,history of hypertension, and previous history of maternal preeclampsia on the incidence ofpreeclampsia, and there is no significant relationship between educational status,employment status, Antenatal Care compliance, history of DM, pregnancy distance, parity,nutritional status, and economic status I mother to the incidence of preeclampsia.